Improving Robustness of Legged Robots Against Mechanical Shock Using Impulsive Dynamics - Driessen, Josephus J. M.; Orsolino, Romeo (Frontiers in Mechanical Engineering, 2021)
This manuscript presents a method to calculate and analyse mechanical shock of a multi-rigid body system, based on the revised concept of the centre of percussion and a newly derived variable called the radius of percussion. The objective is to improve the mechanism's robustness against mechanical shocks that are caused by certain impacts, such as those experienced by legged robots from landing a jump or making a step. In practice, it can be used for placement of shock-sensitive components in robots, such as inertial measurement units and cameras, and for mechanical and controller design improvements and optimizations that aim to reduce shock in certain body parts. Several case studies are presented to support the usefulness of the theory.